AB0310 Ra remission rates with tocilizumab therapy (lornet study: multicentre open-label, phase iv study of the quality of the life patient with severe/moderate ra with adding of tocilizumab to disease-modifying antirheumatic drugs therapy). (23rd January 2014) - Panasyuk, E.; Nasonov, E.; ,
Abstract : Background: Tocilizumab (TCZ), anti-interleukin-6 receptor monoclonal antibody, is an active biological agent for treatment of active rheumatoid arthritis (RA). The main objective of optimal use of TCZ is searching of clinical remission of RA. Objectives: To assess efficacy of TCZ by criteria of remission Disease Activity Score based on 28 joints (DAS28), Simplified Disease Activity Index (SDAI), Clinical Disease Activity Index (CDAI), Health Assessment Questionnaire Disability Index (HAQ-DI) evaluation. Methods: The results come from LORNET study, which is multicentre open-label, phase IV study of the quality of the life patient with severe/moderate RA with adding of tocilizumab (TCZ) to disease-modifying antirheumatic drugs (DMARDs) therapy. Patient had to be naïve to biologics and have moderate to severe active RA (based on the 1987 ACR criteria) to be included in the 6-month trial. A total 201 adult patients with active RA (DAS>3, 2) who remained on stable doses of DMARDs and received TCZ 8 mg/kg every 4 weeks for 24 weeks (total 6 infusions) were enrolled in the study. Mean age of the patients was 49±12 years. And their mean disease duration was 7, 5±6, 5 years. Results: Baseline characteristics of 201 patients included: mean (sd) age 49 (12). Disease duration 7, 5 (6, 5) years, swollen joint count (SJC)16 (9), tender joint count (TJC) 26 (13), HAQ-DI 1, 93±0, 6. Average disease activity score (DAS) 28 of all 201 patients significantly decreased from 6, 75±0, 85 (baseline) to 2, 6±1, 16 (week 24). DAS28 remission (DAS28<2, 6) rate at week 24 being achieved by 51, 3%, SDAI remission – 21, 4%, CDAI remission – 22, 0%. HAQ-DI clinical improvements were seen in patient starting at week 4, delta HAQ-DI -0, 44 (minimal clinical difference is -0, 22). At week 24 delta HAQ-DI -1, 09. There were registered 101 AEs in 51 (25, 4%) patients. Most of AE were mild or moderate. Which were mostly high level transaminases (n=29) and respiratory infections (n=17). 73% of AEs resolved by the time of reporting. There were 15 serious AEs. Conclusions: Tocilizumab in combination with DMARDs is highly effective in the treatment of moderate to severe RA. Tocilizumab infusion is applicable as primary biologic therapy for active RA. Rapid and sustained improvement was noted in quality of life. A manageable safety profile was seen over the 24-week study period. Disclosure of Interest: None Declared